THE NEW PRACTICE OF THE EUROPEAN COURT OF HUMAN RIGHTS IN RELATION TO THE ISSUE OF THE "RIGHT TO EXTENDED CRITICISM" - Pajtić, Bojan; Stefanović, Aleksandra (Zbornik radova Pravnog fakulteta u Novom Sadu, 2025)
Abstract: This article places a particular emphasis on the collision between the right to personal dignity and the right to freedom of expression, particularly in cases where the subjects of criticism are holders of public authority. The European Court of Human Rights has established precedents for the so-called "right to extended criticism," particularly in favour of the public, as most commonly represented through the media. In landmark cases on this matter, a clear distinction has been made between the right to express value judgements regarding a public figure, and the assertion of verifiable facts.In adjudicating the 2021 decision analysed in this paper, the judicial panel took a step back by shifting the right to severe criticism, which typically exceeds the usual boundaries, from the media's domain to the realm of public office holders. Furthermore, the judicial panel materially altered the prior case law by misconstruing the right to make value judgements as the right to disseminate untrue factual claims.